2014
DOI: 10.4103/0976-3147.133595
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid-induced pseudotumor cerebri in acute promyelocytic leukemia

Abstract: All-trans-retinoic acid is an integral part in the treatment strategy of acute promyelocytic leukemia (APL). Here we describe a case of pseudotumor cerebri associated with all-trans-retinoic acid (ATRA) during the induction therapy in an adult with acute promyelocytic leukemia (APL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Including the case presented, the authors identified 23 patients with PTC during ATRA treatment for APL, 11 of whom were adults 8–27,34,35 . Since that publication, an additional three case reports and one case series have been published 4,28,29,36 . Compiling all these patients and our four probable PTC patients (n= 35), the mean age at diagnosis of PTC was 23.5 years with a median age of 18 years, with a female to male ratio of 1.03:1 4,10,28,29,36 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Including the case presented, the authors identified 23 patients with PTC during ATRA treatment for APL, 11 of whom were adults 8–27,34,35 . Since that publication, an additional three case reports and one case series have been published 4,28,29,36 . Compiling all these patients and our four probable PTC patients (n= 35), the mean age at diagnosis of PTC was 23.5 years with a median age of 18 years, with a female to male ratio of 1.03:1 4,10,28,29,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Since that publication, an additional three case reports and one case series have been published 4,28,29,36 . Compiling all these patients and our four probable PTC patients (n= 35), the mean age at diagnosis of PTC was 23.5 years with a median age of 18 years, with a female to male ratio of 1.03:1 4,10,28,29,36 . The mean age of diagnosis amongst these case reports may be an overestimate due to publication bias, as PTC is considered a more common complication in the pediatric population, as seen in our series.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations